1998
DOI: 10.1074/jbc.273.16.9415
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Chaperone α-Crystallin with the Molten Globule State of Xylose Reductase

Abstract: ␣-Crystallin is a multimeric protein that has been shown to function as a molecular chaperone. Present investigations were undertaken to understand its mechanism of chaperoning. For this functional in vitro analysis of ␣-crystallin we used xylose reductase (XR) from Neurospora crassa as the model system. Denaturation studies using the structure-perturbing agent guanidinium chloride indicated that XR folds through a partially folded state that resembles the molten globule. Fluorescence and delay experiments rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
74
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 52 publications
1
74
1
Order By: Relevance
“…But, when a nonnatural substrate carbonic anhydrase remained bound to the chaperone, further loss in subunit exchange rate was Differential Recognition of Natural and Nonnatural Substrate by Molecular Chaperone -Crystallin-A Subunit Exchange Study -Crystallin prevents the aggregation of a large variety of substrates, e.g., insulin, -lactalbumin, lysozyme, conalbumin, alcohol dehydrogenase, citrate synthase, xylose reductase, etc. [9][10][11][12][13][14][15][16][17][18][19] These substrates include proteins, which are of low molecular weight [e.g., insulin (6 kDa)], comparable to -crystallin subunit molecular weight [e.g., carbonic anhydrase (29 kDa)] and high molecular weight [e.g., alcohol dehydragenase (150 kDa)]. Besides, it recognizes substrates under various stress conditions, such as heat, disulphide cleavage, UV light exposure, oxidative stress, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, when a nonnatural substrate carbonic anhydrase remained bound to the chaperone, further loss in subunit exchange rate was Differential Recognition of Natural and Nonnatural Substrate by Molecular Chaperone -Crystallin-A Subunit Exchange Study -Crystallin prevents the aggregation of a large variety of substrates, e.g., insulin, -lactalbumin, lysozyme, conalbumin, alcohol dehydrogenase, citrate synthase, xylose reductase, etc. [9][10][11][12][13][14][15][16][17][18][19] These substrates include proteins, which are of low molecular weight [e.g., insulin (6 kDa)], comparable to -crystallin subunit molecular weight [e.g., carbonic anhydrase (29 kDa)] and high molecular weight [e.g., alcohol dehydragenase (150 kDa)]. Besides, it recognizes substrates under various stress conditions, such as heat, disulphide cleavage, UV light exposure, oxidative stress, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it recognizes substrates under various stress conditions, such as heat, disulphide cleavage, UV light exposure, oxidative stress, etc. [9][10][11][12][13][14][15][16][18][19][20][21] These in vitro substrates belong to no particular category in terms of sequence or threedimensional structure. In addition to these ''nonnatural'' substrates, -crystallin prevents the aggregation of a number of its own substrates, which are present in the lens.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ␣-crystallin has been reported to have autophosphorylation activity by some workers (29,30), whereas others failed detect significant ATPase activity (23). Some spectroscopic (16,24) and proteolytic (31) studies suggested interaction between ATP and ␣-crystallin with concomitant conformational changes, but the nature of the changes and its functional implications are far from clear. According to a totally different viewpoint existing in the literature, most sHSPs having the conserved ␣-crystallin domain have no dependence on ATP for their functions (22).…”
mentioning
confidence: 99%
“…It has already been established that the yield of several substrates refolded in vitro in the presence of ␣-crystallin somewhat increased when ATP was present in the system (16,17,25,26), but mechanistic details are not known. ATP enhanced the yield of ␣-crystallin-mediated refolding of citrate synthase (17,25,26), xylose reductase (16), and luciferase (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation